Estimating Modern Elevations of Pliocene Shorelines Using a Coupled Ice Sheet‐Earth‐Sea Level Model. Issue 9 (28th September 2018) - Pollard, D.; Gomez, N.; DeConto, R. M.; Han, H. K.
Abstract: A coupled ice sheet‐Earth‐sea level model is used to estimate the modern elevations of shoreline features that were formed at high sea level stands during the warm mid Pliocene ~3 million years ago. Knowledge of global mean sea level during this period is important as an indicator of possible future ice sheet retreat and sea level rise. However, local shoreline elevations can deviate from the eustatic mean by various geologic processes over the last 3 million years, including glacial isostatic adjustment of the solid Earth and gravitational field due to both Pliocene ice‐cover changes and more recent glacial cycles. Our coupled model includes glacial isostatic adjustment processes and simulates Antarctic ice sheet, global sea level, and solid Earth variations in the warmest mid‐Pliocene and over the last 40, 000 years. Global maps of estimated modern elevations of Pliocene shoreline markers are produced for a standard radial profile of Earth viscosity and lithospheric thickness. Results are compared to an earlier study with an uncoupled Earth‐sea level model and a different methodology (Raymo et al., Nature Geoscience, 2011, https://doi.org:/10.1038/ngeo1118 ). As in that study, Pliocene shoreline elevations diverge significantly from the eustatic value in widespread regions, especially in the vicinity of present and former ice sheets. In some other regions, elevations are close to eustatic. The results emphasize that care should be taken in interpreting elevations of paleo‐shoreline markers. Key Points: Elevated shorelines formed during the warm mid Pliocene around 3 million years ago suggest considerable Antarctic ice sheet retreat Modern elevations of these shoreline markers have been distorted regionally by glacial isostatic adjustment and other processes A coupled ice sheet‐Earth‐sea level model is used to estimate this distortion, needed for interpretations regarding future sea level rise